An Improved Coordinated Multi-point Multi-user Precoding Algorithm - SUN Zeng-you; LIU Ling-yu (Journal of Harbin University of Science and Technology)
In Long Term Evolution-Advanced ( LTE-A) system，existing coordinated multi-point ( CoMP) multiuser precoding algorithm can not suppress multi-user，intra-user and noise interference at the same time and its computational complexity is high. To solve these two problems，an improved linear precoding algorithm is proposed. Computational complexity，system capacity and bit error rate ( BEＲ) as the indicators were used to evaluate the algorithm performance. We established coordinated multi-point multi-user system model，gave the improved algorithm specific implementation steps，theoretically analyzed computational complexity of the algorithm， and used MATLAB to simulate system performance. Simulation results show that the proposed algorithm can reduce computational complexity and bit error rate to some extent，and the system capacity performance of the proposed algorithm is slightly inferior to that of regularized block diagonalization algorithm.